VD_FINDINFO Décision / 2018 / 934 vom 8. November 2018 - VD Tribunal cantonal (2018)
JUGE UNIQUE, CONTRAVENTION, INDEMNITÉEN GÉNÉRAL, DÉPENS | 29 Cst., 3 al. 2 let. c CPP (CH), 319 CPP (CH), 429 CPP (CH)